DESIGN OF A LOAD BEARING DOUBLE STOREY HOUSE (CORNER LOT - Ismaruby, Zolkifly (Universiti Malaysia Sarawak (UNIMAS), 2001)
This thesis is based on the load bearing walls for a double storey house (corner lot). Load bearing for a double storey house using local clay bricks as the construction material. Walls will carry both imposed and dead load which including the self-weight of the wall. The structures of brick walls are principally designed to resist lateral and vertical loading. The lateral loading arises mainly from the wind pressure acting on the wall. Meanwhile, the vertical loading is attributable to dead load plus imposed load from any supported floors which in this case (double storey house) come from first and ground floor, roofs and self-weight of the wall. The design is based on (B. S. 5628: Part 1: 1992 Code of Practice for Use of Masonry: Part 1: Structural Use of Unreinforced Masonry) and (BS 6399: Design Loading for Buildings, Part 1: Code of Practice for Dead and Imposed Loads). For laterally loaded wall the design is based on the (CP3: Chapter V- Part 2: 1972 Wind Loads)